A laser microdissection-based axotomy model incorporating the use of biomimicking fiber scaffolds reveals that microRNAs promote axon regeneration over long injury distances. (6th October 2020) - Zhang, Na; Lin, Junquan; Chin, Jiah Shin; Zhang, Kunyu; Chew, Sing Yian
Abstract : A laser microdissection-based axotomy model coupled with an aligned electrospun fiber platform was developed, with which the distance of injury site from the cell soma can be precisely controlled. Abstract : The regeneration of injured neurons over long injury distances remains suboptimal. In order to successfully stimulate nerve regrowth, potent biomolecules are necessary. Furthermore, reproducible and translatable methods to test the potency of candidate drugs for enhancing nerve regeneration over long axotomy distances are also needed. To address these issues, we report a novel laser microdissection-based axotomy model that involves the use of biomimicking aligned fiber substrates to precisely control neuronal axotomy distances. Correspondingly, we demonstrate that in the absence of therapeutics, dorsal root ganglion (DRG) explants (consisting of neurons) axotomized within short distances from the main cell somas regenerated significantly longer than axons that were injured more distally ( p < 0.05). However, when treated with a cocktail of microRNAs (miR-132/miR-222/miR-431), robust neurite outgrowth was observed ( p < 0.05). Specifically, microRNA treatment promoted neurite outgrowth by ∼2.2-fold as compared to untreated cells and this enhancement was more significant under the less conducive regeneration condition of a long axotomy distance ( i.e. 1000 μm from the cell soma). Besides that, we demonstrated that the treatment of miR-132/miR-222/miR-431 led to a longer length of nerve regeneration as well as a bigger nerve extension area after sciatic nerve transection injury. These results indicate that distance effects on axonal regrowth may be overcome by the effects of microRNAs and that these microRNAs may serve as promising therapeutics for nerve injury treatment.